Interaction with the Paxillin LD1 Motif Relieves MEKK2 Auto-inhibition - Kahle, Michael P. (J Mol Signal, 2015)
The cell signaling molecule MEK kinase 2 (MEKK2) is a key upstream regulator of MAPK activity that regulates numerous cellular functions, but the mechanisms that control MEKK2 activity are not well understood. Recently, we reported that MEKK2 both binds and promotes ubiquitylation of the scaffold protein paxillin, and thereby modulates the composition of adhesion complexes. In this study, we have extended our examination of this interaction and report that recombinant paxillin is sufficient to induce MEKK2 auto-phosphorylation. Furthermore, we utilize siRNA-mediated paxillin expression knockdown to reveal that MEKK2 activity is reduced in paxillin-deficient cells. Finally, we show that the paxillin leucine-rich motif 1 (LD1) is sufficient to bind to the MEKK2 amino terminal region and activate MEKK2. Taken together, our results show for the first time that paxillin association promotes MEKK2 activation and reveal the existence of a novel bi-directional regulatory relationship between MEKK2 and paxillin.